2017
DOI: 10.1002/ijc.30549
|View full text |Cite
|
Sign up to set email alerts
|

T-cell diversification reflects antigen selection in the blood of patients on immune checkpoint inhibition and may be exploited as liquid biopsy biomarker

Abstract: Cancer immunotherapy with antibodies targeting immune checkpoints, such as programmed cell death protein 1 (PD-1), shows encouraging results, but reliable biomarkers predicting response to this costly and potentially toxic treatment approach are still lacking. To explore an immune signature predictive for response, we performed liquid biopsy immunoprofiling in 18 cancer patients undergoing PD-1 inhibition before and shortly after initiation of treatment by multicolor flow cytometry and nextgeneration T-and B-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 41 publications
1
48
1
Order By: Relevance
“…S14). These results confirm that diversity change within 10% reflects stable TCR repertoire diversity …”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…S14). These results confirm that diversity change within 10% reflects stable TCR repertoire diversity …”
Section: Resultssupporting
confidence: 84%
“…S13a). A previous study also indicated that peripheral blood CDR3 diversity changes within 10% represent a stable‐diversity status and reflect a poor prognosis . Some low frequency T‐cell clones may only be detected once even in the same sample, which may introduce bias to the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…trace the "evolution" of T lymphocytes in response to tumor evolution itself (136,98,137). Thus, recognition of patterns of tumor progression through multiregion biopsy and liquid biopsies might provide new therapeutic strategies tailored to cancer evolution and tumor-microenvironmental background in individual patients.…”
Section: Reviewmentioning
confidence: 99%
“…Checkpoint blockade is seen to induce diversification of T cell receptor repertoire [217] , which has been suggested as a biomarker for PD-1 inhibitor disease stabilization [218] . The assessment of TCR repertoire diversity is becoming increasingly accessible [219] .…”
Section: Monitoring and Modelingmentioning
confidence: 99%